Rethinking Vocational Education and Training: A Systematic Review of Creativity, Innovation, and Skills Development in Sub Saharan Africa. - Obadia Mugabirwe; Benon Muhumuza; Robert Mugabe (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2025)
Vocational Education and Training (VET) systems globally are transitioning from traditional skills-based approaches to innovation-driven models that emphasize creativity, entrepreneurship, and adaptability. This study employs a critical realist systematic literature review (SLR), following PRISMA guidelines, to analyze how creativity and innovation are integrated into VET. The review synthesizes evidence from a curated corpus of literature, including international policy documents and regional studies. It finds that while high-income countries have successfully embedded innovation through dual training systems and strong industry partnerships, VET in Sub-Saharan Africa is constrained by systemic challenges, including a formal TVET completion rate of only 6.5% among youth and high rates of youth not in education, employment, or training (NEET). Theoretical frameworks such as Sen’s Capability Approach and Mezirow’s Transformative Learning Theory support learner-centered pedagogies, yet practical implementation is hampered by fragmented policies, a large informal sector, and a digital divide. To address these gaps, the study proposes an Integrated Framework for Systemic Innovation, which consolidates strategic interventions across four pillars: Policy & Governance, Pedagogy & Curriculum, Institutional Capacity, and Outcomes & Assessment. Actionable policy recommendations include formalizing Recognition of Prior Learning (RPL) for the informal workforce, revitalizing multi-stakeholder Sector Skills Councils, and investing in educator upskilling in digital literacy and maker spaces. The study concludes that sustainable VET reform requires a context-specific balance of global best practices and local realities to drive inclusive economic growth, youth employment, and resilience in the face of technological disruption.